Digital Marketing Communication Strategy of Internet Service Provider Companies in Strengthening Brand Awareness - Rahadian Hastomo; Tria Patrianti; Sa’diyah El Adawiyah (CV. Publikasi Indonesia, 2025)
In the competitive ISP industry, brand awareness is crucial for customer retention and market growth. Digital marketing communication strategies offer a powerful tool to enhance brand visibility, yet their effectiveness for ISPs remains underexplored. This study examines how ISPs in Indonesia utilize digital communication channels to strengthen brand awareness, identifying key strategies and their impact. A quantitative approach was employed, with data collected from 500 internet users via stratified random sampling. A validated questionnaire measured variables like social media engagement, email marketing, and brand recall. SPSS software facilitated descriptive and regression analyses. Results indicated that social media (69.04% adoption) and banners (47.37%) were the most effective channels, with content relevance and interactivity significantly boosting brand recognition (p < 0.05). Challenges included misinformation risks and low engagement in email campaigns. The study underscores the need for ISPs to prioritize interactive, platform-specific content and integrate metrics-driven campaigns. Policymakers and marketers can leverage these insights to design targeted digital strategies, fostering trust and loyalty in a dynamic market.